The answer too your question is 65 it is equal to the square root of 65
Answer:
it has one solution
Step-by-step explanation:
1.y=x-3
2. 3y-3x sub x-3 in place of y therefore
it can also be written as 3x-3x-9=9
if you add 9 to both sides 3x-3x-9+9=-9+9
0+0=0
The answer to this delightful exsubruent question is 5
Answer:
-503
Step-by-step explanation:
the statement tell us:
(r - 5)^3 + r^2
r= -3
so we have:
(-3 - 5)^3 + (-3)^2
(-8)^3 + 9
-512+9 = -503
Yes this answer is reasonable since 47 divided by 11 is close to 4. The answer is 4 2/71